1994
DOI: 10.1007/bf01958985
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal intracranial lesions following placenta abruption

Abstract: A case-controlled study of the cerebral ultrasound appearances of neonates following placental abruption was undertaken. Twenty-nine index subjects (median gestation 29 weeks) were identified over a 2-year period with gestation- and sex-matched controls. Placental abruption was associated with a four-fold increased incidence of periventricular leukomalacia and extensive periventricular haemorrhage, without increased mortality. Ten infants (34%) developed cystic periventricular leukomalacia following placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several studies have reported an increased morbidity and mortality among preterm neonates born to women with chorioamnionitis or abruption compared to preterm neonates born without these complications [1,5]. In the current study, the only factor that accounted for this difference was gestational age at delivery.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Several studies have reported an increased morbidity and mortality among preterm neonates born to women with chorioamnionitis or abruption compared to preterm neonates born without these complications [1,5]. In the current study, the only factor that accounted for this difference was gestational age at delivery.…”
Section: Discussionmentioning
confidence: 43%
“…Management may differ according to the underlying etiology as well as prognosis. Several studies reported that fetuses born to women with chorioamnionitis or placental abruption may develop multiorgan involvement and are at increased risk for long-term neurological complications [4,5]. Therefore, neonatal morbidity is not only related to prematurity, but also to the etiology responsible for the development of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…However, placental examination may reveal the cause of the etiological factors leading to cystic encephalomalacia in the fetus, which include: placenta previa, abruptio, abnormalities in placental circulation and tell-tale signs of infections. [15][16][17] The sequence of events leading to the formation of cysts begins with liquefactive necrosis of the brain parenchyma, which forms the acute phase lasting about 8 to 24 hours. This is followed by a subacute inflammatory phase of 3 to 5 days, which is characterized by macrophage infiltration, rimming by reactive astrocytes, and formation of axonal spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…Chances of development of cystic periventricular leucomalacia or intraventricular haemorrhage are higher in neonates born after severe placental abruption. 16,17 The risk increases with prematurity and low birth weight. Severe placental abruption increases the risk for cerebral palsy and it is also linked with sudden infant death syndrome.…”
Section: Discussionmentioning
confidence: 99%